ANALYSIS OF PINOCCHIO CHARACTER IN PINOCCHIO (2022) MOVIE - Suryati, Ninda; Damayanti, Indah; Kurniawan, Ildi (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2025)
The purpose of this study is to describe the main character in Pinocchio (2022) movie. This type of research is qualitative descriptive or this research is dialog and scenes that show character in the main character. The data source in this research is Pinocchio (2022) movie by Chris Weitz. This movie is an adaptation of the previous movie entitled Pinocchio (1940). The method used in this research is qualitative description by using Robert Stanton's character analysis theory (1965). The data collection technique uses watching, listening, classifying, analyzing, and concluding data. The results of the analysis show that the character of the main character Pinocchio contained in the movie Pinocchio (2022) are; disobedient character (8), loving character (5), obedient character (5), curious character (4), naive character (4), cheerful character (1), worrying character (4), lying character (4), brave character (2), friendly character (3), intelligent character (2), optimistic character (2), responsible character (2), helpful character (1), and fearful character (1). The most dominant character of Pinocchio is the dissident character. Meanwhile, the characters that were least encountered by the researcher were cheerful, helpful, and fearful. The results of this study reveal that the Pinocchio (2022) movie is child-friendly and safe from harmful meanings that may be implied in the movie. However, there is also a need for parental supervision.